2021
DOI: 10.1108/ijoem-04-2021-0555
|View full text |Cite
|
Sign up to set email alerts
|

What effect did the Green Credit Policy have on China's energy or emission intensive firms?

Abstract: PurposeThe role of energy or emission intensive firms face contradictory demands from advancing economic development and environmental improvement and protection and thus require appropriate policy interventions to balance the two needs. China's “Green Credit” policy that restricts loans to energy or emission intensive firms provides an example to study the impact of these kinds of policy intervention.Design/methodology/approachUsing the data of all A-share listed companies in Shanghai and Shenzhen stock excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…For example, Peng and Zheng (2021) have found that green finance significantly improves energy efficiency, regional resources, economic development, and the degree of marketization all of which influence this significant positive effect. Zhang Q et al (2021) have confirmed that GCGs are essential in mitigating sulfur dioxide and wastewater emissions. Tian et al (2022) have found that by directing the flow of funds, green credit policies can support green technology innovation in heavy polluting industries, thus supporting the development of green industries while curbing emissions from polluting industries.…”
Section: Empirical Reviewmentioning
confidence: 79%
See 2 more Smart Citations
“…For example, Peng and Zheng (2021) have found that green finance significantly improves energy efficiency, regional resources, economic development, and the degree of marketization all of which influence this significant positive effect. Zhang Q et al (2021) have confirmed that GCGs are essential in mitigating sulfur dioxide and wastewater emissions. Tian et al (2022) have found that by directing the flow of funds, green credit policies can support green technology innovation in heavy polluting industries, thus supporting the development of green industries while curbing emissions from polluting industries.…”
Section: Empirical Reviewmentioning
confidence: 79%
“…For example, Liu et al (2022) demonstrated that the Chinese energy sector receives an overall excessive level of green investment (overinvestment) when compared with the estimated optimal investment level. Zhang Q. et al (2021) found that GCGs affect the size of loans to environmentally friendly manufacturing firms, with small-and medium-sized firms receiving more loans than larger ones. Liu et al (2019) have confirmed that the debt financing capacity in heavily polluting enterprises significantly reduces because of the GCGs.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of environmental regulations on GTFP is studied using the linear probability and the proportional hazards models (Ai et al, 2020), systematic generalized estimation method (GMM), dynamic count data model (Bitat, 2018), difference-in-difference (DID) model (Zhang et al, 2021), bootstrap panel Granger causality test (Liu et al, 2021), spatial model (Peng, 2020) and evolutionary game theory (Ulph, 2000). It is concluded that environmental regulations have an "innovation compensation effect," thus, increasing productivity.…”
Section: Review Of Research Methodsmentioning
confidence: 99%